Affordable and high-quality outpatient adult medical care - Love, Richard R; Salim, Reza (Bangladesh Journal of Medicine, 2019)
In low- and middle-income countries (LMIC) like Bangladesh, hospitalization-requiring care for all is usually adequately provided by public institutions for poorer, and private hospitals for wealthier citizens. In contrast, outpatient medical care and pharmaceuticals require out-of-pocket payments by patients. How to provide such services which are affordable and of effectively high-quality, has been difficult to define. With increasing non-communicable disease (NCD) case-burdens in cancer and cardiovascular diseases in LMIC/Bangladesh, addressing these service challenges is becoming more urgent. We have been working to provide medical care for women with breast problems and have identified in this setting the following components as critical to meeting this affordability/quality challenge: 1. Maximal use of information technology tools; 2. Increased paraprofessional staffing; 3. Diagnostic pathways and care guidelines which are evidence-based.; 4. Increased point-of-care diagnostic services; and 5. Implementational research. While broad societal issues of poverty, human rights, governance, and education strongly influence the quality of medical care, local systemic solutions are needed if the 2030 WHO Sustainable Development Goal of lowering morbidity and mortality from NCDs by one third, is to be met. Bangladesh J Medicine Jan 2019; 30(1) : 44-49